Steam reforming of glycerol over Ni/Mg/γ-Al 2O 3 catalysts. Effect of calcination temperatures - Dieuzeide, María Laura (2012)
The aim of this work is to study the catalytic activity of Ni(10%) based catalysts supported over ã-Al 2O 3 modified with Mg (3%) for the steam reforming of glycerol. Catalysts have been prepared by incipient wetness impregnation method; analysing the effect of the calcination temperature of the modified support and the calcination temperature of the catalysts. Catalysts were characterized by temperature programmed reduction, (TPR), x-ray diffraction (DRX) and BET surface area. All catalysts were tested for this reaction in a fixed bed reactor. The best performance was achieved with the catalyst calcined at 500 °C being the optimum calcination temperature for the modified support of 900 °C This behaviour is ascribable to the formation of MgAl 2O 4 spinel which favours the dispersion of Ni°, responsible of the catalytic activity. © 2012, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.